Notes on Candelariella reflexa s. str. (Ascomycota, Candelariaceae) in Poland - Dariusz Kubiak (Acta Mycologica, 2024)
This paper presents new localities of the epiphytic lichen Candelariella reflexa (Nyl.) Lettau found in NE Poland. The species has been reported in Poland for over two decades, but the progress of research on the taxonomy of this genus requires confirmation of the data by the currently accepted taxonomic approach. The paper also discusses the diagnostic features of the species that help distinguish it from other similar taxa.